Consumer rights and freedom of movement– rights of persons with disabilities in relation to travel by air - Mokhtar, Khairil Azmin; Md Tah, Ikmal Hisham (2017)
Travelling by airplane, which is less time consuming and almost a necessity for long distance, is commonplace nowadays. The transportation by air includes all types of passengers including persons with disabilities. Freedom of movement is proclaimed in international treaties, Federal Constitution of Malaysia and disability-related laws. For the purpose of realizing right to travel, Malaysia Aviation Commission (MAVCOM) has enacted Malaysian Aviation Consumer Protection Code 2016 to strengthen the consumer protection for persons with disabilities. In this paper the legal position of international and domestic laws which are related to and available for airline passengers with disabilities as well as the newly promulgated Malaysian Aviation Consumer Protection Code 2016 are evaluated. This study comes up with the finding that the code enhances legal protection for disabled airline passengers from being discriminated and confers benefits to all stakeholders in upholding their rights.